Dampak Paparan Panas di Lingkungan Kerja Terhadap Kesehatan Pekerja - Reinita Aulia; diana mayasari; fitria saftarina (Medula, 2023)
Heat exposure occurs when the body absorbs more heat than can be received through the process of thermoregulation. Workers who are exposed to heat or work in a hot environment may be at risk of experiencing heat stress which can adversely affect the worker's health. Heat exposure can cause physiological responses from various organs and cause various health problems. This article aims to discuss the impact of heat exposure in the work environment on the health of workers and preventive strategies that can be done. Heat exposure is a contact between an individual and the environment which can pose a risk of increased body temperature and perceived discomfort. Through the high frequency and intensity of heat waves, exposure to heat can cause physiological responses to various systems, namely the central nervous, musculoskeletal cardiovascular, and integumentary systems which if not properly controlled can lead to pathological conditions. Health problems that can occur are heat stroke, heat exhaustion, heat syncope, heat cramp and heat rash. Several steps must be implemented to protect the health of workers from exposure to heat in the work environment so that workers are not at risk of experiencing work-related injuries or illnesses.